An implant periapical lesion associated with an endodontic-periodontic lesion of an adjacent molar - Ting-An Chou; Yu-Liang Chang; Ling-Min Yu; Whei-Ling Pan; Yuh-Ren Ju; Chiu-Po Chan (Elsevier, 2010)
Adjacent natural teeth with untreated pulpal or periodontal pathology may be a potential risk for implant infection. We report a rare case of an implant periapical lesion (IPL) possibly caused by direct extension of a periradicular lesion of an adjacent tooth. A 40-year-old female patient, who had previously received three implants on the edentulous areas of teeth 16, 36 and 46, had a recurrent infection over the lower left second molar area for 2 years. A periapical radiograph revealed incomplete root canal treatment and an infrabony defect on the mesial side of the lower left second molar; the defect extended to the apical third of the adjacent implant on tooth 36. Open flap debridement was performed 1 year after implant placement, but pain and swelling persisted for another year. Therefore, the second molar was extracted at the patient's request. The patient was unable to seek earlier and prompt treatment as she was abroad; therefore, we were able to observe the progression of severity in the IPL. One year after the extraction, the symptoms had subsided, and a periapical radiograph showed that the radiolucent lesion had decreased in size. She was followed for another 1.5 years and showed marked improvement. In this case, the IPL probably originated from the endodontic-periodontic problem of the adjacent molar, and the infected implant was saved by removing the infection source. We also discuss the treatment and prognosis of IPLs. To prevent the occurrence of an IPL, it is important to evaluate the pulpal and periodontal status of the teeth near the implant site when making a comprehensive treatment plan for an implant.